Functioning Expressive Speech Acts in the 2019 Indonesian Presidential Election Debates - Azwar Abbas; Djatmika Djatmika; Sumarlam Sumarlam; Joko Nurkamto (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This study aimed at investigating and explaining how the expressive speech acts functioned and differed in use among the candidates. A case study research design was employed. The data were the formal forms of expressive speech acts, lingual markers, and contexts. The sources were videos of five debate programs containing utterances, conversations, or dialogs made by both candidates. Candidates 01 belonged to Jokowi-Ma’ruf Amin, while candidates 02 belonged to Prabowo-Sandiaga Uno. Non-participatory observation and documentation techniques were used to collect data, and then they were analyzed using the content analysis model. Findings show sixteen functions of the expressive speech acts, namely, thanking, greeting, apologizing, blaming, praising, regretting, complaining, criticizing, expressing hopes, agreeing, disagreeing, expressing optimism, expressing wants, insinuating, making jokes, and appreciating. Then, candidates had different tendencies in functioning these expressive speech acts. Both candidates used greeting, apologizing, praising, complaining, disagreeing, expressing optimism, expressing wants, and making jokes almost equally. Then, candidate 01 tended to express hopes and insinuate, while candidates 02 were to thanking, blaming, regretting, criticizing, thanking, agreeing, and appreciating. Finally, in the 2019 Indonesian presidential election debate, both candidates functioned the speech acts still with Indonesian norms and values.